2020
DOI: 10.1093/jcmc/zmaa014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internet and Social Media Use on Well-Being: A Longitudinal Analysis of Adolescents Across Nine Years

Abstract: The present research examines the longitudinal average impact of frequency of use of Internet and social networking sites (SNS) on subjective well-being of adolescents in Germany. Based on five-wave panel data that cover a period of nine years, we disentangle between-person and within-person effects of media use on depressive symptomatology and life satisfaction as indicators of subjective well-being. Additionally, we control for confounders such as TV use, self-esteem, and satisfaction with friends. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 46 publications
3
68
0
5
Order By: Relevance
“…Youth focus on relationships and the ability to control their narratives and make decisions about their own lives. The view of foster youth is supported by a growing body of longitudinal studies suggest no relationship between negative mental health outcomes and ICT use for adolescents (Orben & Przybylski, 2019a, 2019bSchemer, Masur, Geiß, Müller, & Schäfer, 2020). Although additional research is needed related to ICT use by foster youth in particular, it is noteworthy that other marginalized youth, including homeless youth (Barman-Adhikari, Bowen, Bender, Brown, & Rice, 2016;Rice & Barman-Adhikari, 2014) and LGBTQ youth (McInroy, McCloskey, Craig, & Eaton, 2019) are found to benefit relationally, and in other domains, from social media and other ICTs.…”
Section: Discussionmentioning
confidence: 99%
“…Youth focus on relationships and the ability to control their narratives and make decisions about their own lives. The view of foster youth is supported by a growing body of longitudinal studies suggest no relationship between negative mental health outcomes and ICT use for adolescents (Orben & Przybylski, 2019a, 2019bSchemer, Masur, Geiß, Müller, & Schäfer, 2020). Although additional research is needed related to ICT use by foster youth in particular, it is noteworthy that other marginalized youth, including homeless youth (Barman-Adhikari, Bowen, Bender, Brown, & Rice, 2016;Rice & Barman-Adhikari, 2014) and LGBTQ youth (McInroy, McCloskey, Craig, & Eaton, 2019) are found to benefit relationally, and in other domains, from social media and other ICTs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jensen et al (30) found that baseline frequency of social media use did not predict increased daily depressive symptoms at 1-to 2-year followup in a demographically representative sample of adolescents. More prolonged studies spanning 8 or 9 years have further corroborated the view that frequency of social media use does not longitudinally predict depressive symptoms in adolescents even when studied across developmental periods from adolescence to young adulthood (31,32). Further, using a longitudinal panel design on a sample of American adults, Hampton (33) showed that social media use was in fact associated with reduced psychological distress due to the social opportunities afforded by social networking sites.…”
Section: Longitudinal Findingsmentioning
confidence: 92%
“…We emphasize that this evidence is overwhelmingly based on self-reports and refers to between-person correlations, not causation. Based on a recent systematic review (Course-Choi & Hammond, 2021) and additional research, we also note that longitudinal panel studies to date find little to no evidence for positive or negative long-term effects of social media screen time on mental health in general (Orben et al, 2019;Schemer et al, 2020; but see Shakya & Christakis, 2017). However, some longitudinal evidence for negative effects on body image among adolescents exists (Course-Choi & Hammond, 2021).…”
Section: Social Media and Mental Health: The State Of The Fieldmentioning
confidence: 94%